Forest-Dependent Communities and Livelihood Diversification: A Case Study - Mahdavi, Leila; Hashemi, Fatemeh; Yazdani, Sahar (Journal of Selvicoltura Asean, 2024)
Forest-dependent communities face significant challenges due to environmental changes and economic pressures. Understanding how these communities diversify their livelihoods is crucial for enhancing their resilience and sustainability. This study aims to examine the strategies employed by forest-dependent communities to diversify their income sources and reduce reliance on forest resources. A qualitative case study approach was utilized, involving in-depth interviews and focus group discussions with community members in a selected forest-dependent area. The findings reveal that communities engage in various livelihood diversification strategies, including agriculture, handicrafts, and eco-tourism, to mitigate risks associated with forest dependency. Additionally, the study highlights the importance of social networks and local knowledge in facilitating successful diversification. The results indicate that while diversification has improved economic stability, challenges remain, including limited access to markets and resources. The study concludes that promoting livelihood diversification among forest-dependent communities is essential for enhancing their resilience and sustainability. Policymakers should focus on supporting these communities through capacity-building initiatives and improving access to markets and resources.